PENGARUH INTENSITAS PEMOTONGAN TERHADAP PRODUKTIVITAS Indigofera zollingeriana - Wagiu, Ivan H.G.M.; Kaunang, Ch.L.; Telleng, M.M.; Kaunang, W.B (ZOOTEC, 2020)
THE EFFECT OF DEFOLIATION INTENSITY ON PRODUCTIVITY OF Indigofera zollingeriana. This research aims to know the effect of defoliaion intensity on productivity (fresh production, dry weight production, proportion of leaves and stems) and to know the defoliation intensity with optimal productivity of forage Indigofera zollingeriana. This research was conducted in December 2019 until March 2020. It consisted of defoliation intensity at 75cm (T75), 100cm (T100), 125cm (T125), and 150cm (T150). The design used in this experiment is Completely Randomized Design. The variables in this research were 1. fresh production leaves and stems; 2. dry weight production leaves and stems; 3. the proportion of leaves and stems dry weight production of forages Indigofera zollingeriana. The results showed that the difference of intensity defoliation had a significantly effect (P<0,01) on productivity (fresh production, dry weight production, proportion of leaves and stems) forage Indigofera zollingeriana. Defoliation intensity 75 cm have significantly (P<0,01) fresh and dry weight leaf of Indigofera zollingeriana than hight defoliation 125 cm and 150 cm. Intensity defoliation 125 cm have significantly (P<0,01) leaf-stem ratio of Indigofera zollingeriana than any other. It conclude that intensity defoliation 125 cm have highly productivity. Â Â Keywords: Indigofera zollingeriana, cutting intensity, productivity